Invariable (2x2) Linear Systems - Ramadhan, Ayad M.; Jabbar, Adil K. (Sulaimani Journal for Pure and Applied Sciences, 2002)
This paper discusses a new type of (2x2) linear systems called invariable system, which depends on the determinants idea. Also, it gives a relation between the solution of the original system and the system after changing (bj's).
Keywords: Linear; Invariable; Determinants